2019
DOI: 10.1007/s11187-019-00275-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender (in)equality within the household and business start-up among mothers

Abstract: Using data on all businesses started by mothers of young children in Sweden between 2000 and 2014, we explore which factors are associated with entrepreneurship among mothers. We find that being unemployed or being an immigrant is positively associated with business start-up by mothers; however, our findings show that what matters more is the paternity leave taken by the mothers' partners. These findings suggest that in institutional contexts such as Sweden, gender inequality is not a persistent feature of mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 72 publications
0
17
0
8
Order By: Relevance
“…There is some debate exploring how entrepreneurship is influenced by different forms of institutional support for working parents regarding paid leave and subsidised child care (Naldi et al, 2019;Thébaud, 2015). In the case of the UK, parents in employment can access paid maternity, paternity and parental leave.…”
Section: The Uk Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…There is some debate exploring how entrepreneurship is influenced by different forms of institutional support for working parents regarding paid leave and subsidised child care (Naldi et al, 2019;Thébaud, 2015). In the case of the UK, parents in employment can access paid maternity, paternity and parental leave.…”
Section: The Uk Contextmentioning
confidence: 99%
“…Our study has a number of limitations which offer scope for further research. We employed a single country sample which limits generalisability; thus, as Naldi et al (2019) revealed in their analysis of Sweden, under some circumstances, generous parental leave can make space for women to pursue entrepreneurship if spouses share caring duties over a sustained period of time. Thus, a more nuanced analysis of how differing institutional contexts policies affect exit are required.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos hallazgos, entre otros, concuerdan con la teoría liberal feminista, al argumentar que si las mujeres tuvieran igualdad de oportunidades que los hombres en educación, experiencia laboral, entre otros, podrían tener comportamientos similares en relación con el crecimiento y tamaño de sus iniciativas de negocios (Naldi et al, 2019). Trabajos basados en esta perspectiva demuestran que los hombres poseen un alto nivel de autoafirmación, de autoexpansión y necesidad de dominar; y las mujeres tienen altos niveles de desinterés, preocupación por los demás y sensibilidad interpersonal, características que influyen en la financiación, el tamaño y tipo de emprendimientos y los rendimientos futuros (Clancy, 2007;Eagly y Wood, 1991).…”
Section: Fundamentación Teóricaunclassified
“…Such women have greater control over their work schedules in ways that are more conducive to childrearing. Both the popular literature and academic studies have identified women taking on the role of “mumpreneurs” as a strategy for working while raising a family (Duberley & Carrigan, 2012; Jean & Forbes, 2012; Kirkwood, 2009; Naldi, Bau, Ahl, & Markowska, 2019; Nel, Maritz, & Thongpravati, 2010). In this sense, self‐employment acts as a mechanism to increase the odds of having children.…”
Section: Concepts and Theorymentioning
confidence: 99%